2009
DOI: 10.1103/physreva.79.052323
|View full text |Cite
|
Sign up to set email alerts
|

Creation of high-quality long-distance entanglement with flexible resources

Abstract: We present a quantum repeater protocol that generates the elementary segments of entangled photons through the communication of qubus in coherent states. The input photons at the repeater stations can be in arbitrary states to save the local state preparation time for the operations. The flexibility of the scheme accelerates the generation of the elementary segments (close to the exact Bell states) to a high rate for practical quantum communications. The entanglement connection to long distances is simplified … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 30 publications
0
85
0
1
Order By: Relevance
“…Although a lot of works have been studied in the area of cross-Kerr nonlinearity [25,27,[30][31][32][33][34][35][36][37][38][39][40], we should acknowledge that it is still a quite controversial assumption for a clean cross-Kerr nonlinearity in the optical single-photon regime. In 2002, Kok et al pointed out that the Kerr phase shift is only τ ≈ 10 −18 in the optical single-photon regime [44,45].…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Although a lot of works have been studied in the area of cross-Kerr nonlinearity [25,27,[30][31][32][33][34][35][36][37][38][39][40], we should acknowledge that it is still a quite controversial assumption for a clean cross-Kerr nonlinearity in the optical single-photon regime. In 2002, Kok et al pointed out that the Kerr phase shift is only τ ≈ 10 −18 in the optical single-photon regime [44,45].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In this section, we will introduce the cross-Kerr nonlinearity to construct QND, which can also be used to implement this protocol. Cross-kerr nonlinearity has been widely studied in the construction of CNOT gate [30], performance of complete Bell-state analysis [31], entanglement purification [13] and so on [32][33][34][35][36][37][38][39][40]. The Hamiltonian of a cross-Kerr nonlinear medium can be written as H = χn anb .…”
Section: Single-photon-assisted Entanglement Concentration With mentioning
confidence: 99%
“…From Equation (50), the entanglement will be degraded after the entanglement connection, as shown in Figure 10. If we consider the case that we perform the entanglement swapping for n times to connect the entanglement between the remote locations, A and K, we will get:…”
Section: Entanglement Concentration For Single-photon Entanglementmentioning
confidence: 99%
“…Figure 1 is the basic construction of the parity-check gate, which was first proposed by Nemoto and Munro in 2004 [43]. It is also a powerful element in current quantum information processing, such as Bell state analysis [46][47][48], entanglement purification [22][23][24], and so on [49][50][51][52]. Let us suppose that two polarization qubits, a1 and a2, are initially in the state:…”
mentioning
confidence: 99%
“…The previous works indicated that QNDs with a crossKerr medium and a coherent state can be used for operating the controlled-not (CNOT) gate [24,25] and singlephoton logic gates with minimal sources [26], entanglement purification and concentration [27,28]; generating high-quality entanglement [29,30], and qubits [31][32][33]; and analyzing the Bell states with the polarization degree of freedom [34]. In general, cross-Kerr nonlinearities can be described with the Hamiltonian as [24,34] …”
Section: Hbsa Protocol For Bell States In Spatial Modesmentioning
confidence: 99%